The impact of a pharmacist‐designed mobile application on blood pressure control and medication adherence in patients with hypertension. Issue 7 (3rd August 2020) - Manigault, Kendra R.; McKinley, DeAngelo; Patel, Sweta; Truong, Ca; Nguyen, Sim; Akil, Ayman; Newsom, Lydia; Murnane, Kevin S.; Thurston, Maria Miller
Abstract: Introduction: Mobile applications (apps) may improve adherence and disease state‐related outcomes in patients with uncontrolled chronic diseases, including hypertension. Objective: The purpose of this study was to determine the effectiveness of using a pharmacist‐designed app to improve blood pressure (BP) and promote adherence to antihypertensive medications. Methods: This study was a prospective, multicenter, randomized controlled trial. Patients were randomized to an intervention or control group for 3 months. The intervention was a pharmacist‐designed mobile app. Antihypertensive medication refill history was assessed 3 months before, during study, and 3 months after study completion. Continuous outcome measures investigated were systolic/diastolic BP and medication refill history using the cumulative medication gap (CMG). Statistical analysis comparing median difference in BPs and CMGs between groups was conducted using Theil‐Sen Siegel regression. Results: The propensity score adjusted population consisted of 78 patients (n = 39 for both groups). No significant difference was observed in the conditional median difference in CMG between groups at the 3‐month follow‐up visit (−0.06 [ P = .70]). No significant difference was observed in the conditional median difference in systolic and diastolic BP between groups at the 3‐month follow‐up visit (−2.00 [ P = .07] and −1.00 mmHg [ P = .39] systolic and diastolic, respectively). Upon subgroup analysis, those nonadherent at baseline in the intention to treat population experienced a significant improvement in outcomes (−0.06 P = .03] and −12.00 mmHg [ P = .002] CMG and systolic BP, respectively). Conclusion: A pharmacist‐designed mobile app did not result in improved medication adherence or BP control, but may be beneficial in patients with hypertension who struggle with medication adherence.